Variability of wintering oat hoodness under the influence of external environmental conditions - M. V. Kuzenko (Новые технологии, 2023)
The article presents the results of assessment of varieties and lines of wintering oats cultivated in the soil and climatic conditions of the Republic of Adygea from the competitive variety trial nursery on the content of the husk depending on environmental factors.For comparison, agricultural years of 2017-2018 and 2021-2022 have been taken; they differ in the phase of plant development before leaving for winter and the amount of precipitation in the springsummer period. In the course of the research, generally accepted methods have been used, including «The Guidelines for the Study and Preservation of the World Collection of Barley and Oats» and GOST 10843- 76. A detailed analytical review of climatic conditions in the study period has been given, weather conditions compared with the main phases of plant growth and development, and their influence on lodging resistance and filminess of wintering oats noted. The rates of onset of heading phase and wax ripeness of grain have been analyzed, the difference in the date of their onset by years determined.As a result, data have been obtained on the husk content in oat grain per year with sufficient and excessive moisture, and the group and range of husk content variation determined. It was established that during the research period, the variability of hoodness from agrometeorological conditions was 7-8%, and from varietal characteristics 1-4%. In a year with excess moisture, the percentage of varieties with an average husk content increases, and the number with a low content of it decreases. All varieties and lines of overwintering oats have low and medium grain hoodness. Samples with low and medium content of husk, which keep this economically valuable trait stable and unchanged in years with different amounts of precipitation and are of interest for further breeding work have been selected.